PENGEMBANGAN PERIKANAN - Meyzi Heriyanto, Wira Sastra, Sujianto, (Jurnal Ilmu Administrasi Negara, 2019)
Fisheries Development. The research objective is to determine the implementation ofdevelopment in Kampar District. The research informants were the Head, Secretary and Head ofSection, Head of Section and Head of Subdivision of the Head of Regional Office, Members ofDPRD, UPT Train and Fish Culture Development Farmer Group. Data collection techniques areinterviews and observation. Data analysis through data collection, data reduction and conclusiondrawing. Factors that influence Fisheries Development in Kampar Regency consist of ConflictingGoals, Communication factors, Conflicting factors which are suppressed Cooperation Factors,Competition Factors, Decision Making factors, Response factors to Changes As well as in effortsto increase motivation can be done is to optimize staff performance .